Conflict of honors - Lee, Sharon, 1952-; Miller, Steve, 1950 July 31- (Lee, Sharon, 1952- Liaden universe., 2019)
"When Priscilla Delacroix y Mendoza was sixteen years old, she was declared dead by the High Priestess of the Goddess and by her mother. Banished to survive on her own, Priscilla has roamed the galaxy for ten years as an outcast -- to become a woman of extraordinary skill ... Now an experienced officer assigned to the Laiden vessel Daxflan, she's been abandoned yet again. Betrayed by her captain and shipmates, she's left to fend for herself on a distant planet. But Priscilla is not alone. Starship captain Shan yos'Galan is about to join Priscilla's crusade for revenge. He has his own score to settle with Daxflan. But confronting the sinister crew will be far easier -- and safer -- than confronting the demons of Priscilla's own mysterious past."--Page 4 of cover